Influence of Hypnotherapy to Reduce the Anxiety of School-Age Children in the Preoperative Phase in the Guntur Room of Level II Dustira Cimahi Hospital - Nurmansyah, Andri; Iskandarsyah, Aulia; Sriati, Aat; Yani, Fifi Siti Fauziah (STIKep PPNI Jawa Barat, 2022)
Aims: Preoperative anxiety in school-age children is an important problem for children who will carry out major surgery. When not resolved the problem results in a negative postoperative response such as higher pain, impaired sleep patterns, no appetite and changes in maladaptive behavior over the next two weeks. Pharmacological therapy is not given to psychosocial problems related to anxiety in school-aged children. So, it is necessary to trace the results of research related to non-pharmacological therapy. One of the non-pharmacological therapies used is Hypnotherapy. This study aims to analyze the effect of hypnotherapy in reducing anxiety in the preoperative phase by using the Modified Yale Preoperative Anxiety Scale (mYPAS) instrument. Hypnotherapy intervention is carried out structurally in the preoperative phase. Methods: This type of research is a Quasy Experiment with a time series design research design through pretest and posttest one group design. The technique used in this study was purposive sampling with 24 samples. Analysis of the data used consisted of univariate and bivariate. Univariates in this study describe the median while bivariate use Wilcoxon. Results: The results of the statistical analysis showed a significant difference between the anxiety test before and after the hypnotherapy intervention was given (p-value 0,0001). Conclusion: Influence of hypnotherapy to reduce the anxiety of school-age children in the preoperative phase in the Guntur room of level II Dustira Cimahi Hospital. Suggestions for nurses are expected to develop science and skills in complementary nursing and can be used as a companion intervention in overcoming preoperative anxiety in children.